Cobalt-Containing Dispersion Catalysts for Three-Phase Fischer–Tropsch Synthesis - Maximov, Anton Lvovich; Kulikova, Mayya Valerevna; Dementyeva, Oksana Sergeevna; Ponomareva, Anna Konstantinovna (Frontiers in Chemistry, 2020)
New dispersed cobalt catalysts for Fischer-Tropsch synthesis (FTS) were synthesized in present work. Dispersed cobalt phase was prepared in heavy paraffin medium using ex situ and in situ approach through thermal decomposition of nitrate precursor at various temperatures. It was shown that an increase in the temperature of catalytic suspension formation from 215 to 260 °C lead to enlargement of the particles of the dispersed phase from 190 to 264 nm, which was probably due to enhanced agglomeration at elevated temperatures. Rheological properties of obtained catalytic suspensions can be described by Binham equation; moreover, concentration of dispersed phase has a direct impact on the structure of the whole catalytic system. Ultrafine suspensions of Pd-promoted catalytic systems were tested in FTS synthesis. Overall yield of С5+ hydrocarbons was up to 50 g/m3 and the productivity of these catalytic systems reached 270—290 g/kgCo h​